Finite Impulse Response Errors-In-Variables System Identification Utilizing Approximated Likelihood and Gaussian Mixture Models - Orellana-Prato, R (Institute of Electrical and Electronics Engineers Inc., 2023)
In this paper a Maximum likelihood estimation algorithm for Finite Impulse Response Errors-in-Variables systems is developed. We consider that the noise-free input signal is Gaussian-mixture distributed. We propose an Expectation-Maximization-based algorithm to estimate the system model parameters, the input and output noise variances, and the Gaussian mixture noise-free input parameters. The benefits of our proposal are illustrated via numerical simulations. © 2013 IEEE.